PRINCIPLES OF CREATING AN IDEOFRAPHIC DICTIONARY OF MAKING UP THE SEMANTIC FIELD OF LEXEMES “ORGANIC WORLD” AND “FOOTBALL” IN UZBEK, ENGLISH AND RUSSIAN LANGAUGES (World Bulletin of Social Sciences, 2022)
Since the semantic field is considered to be the representation of images of language divided into meaningful categories in our mind, it is effective to interpret the words in the ideographic dictionary into smaller microfields within the fields. According to the theories of ideographic vocabulary, interpreting words on the basis of relatedness helps to quickly develop an idea about something. The basis of ideography is onomasiology, that is, the theory of form to content, therefore, in the article of the ideographic dictionary, verb lexemes are analyzed as having the same level of use as noun lexemes
Keywords: Organic world; ideographic vocabulary; verb lexemes